Pemanfaatan Paket Genetika dalam Pembelajaran Pewarisan Sifat untuk Meningkatkan Motivasi dan Hasil Belajar Siswa - Eddy Ilhamsyah (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
This research is a classroom action research that takes place in 2 (two) cycles, with the aim of knowing whether the use of the genetics package can increase the motivation and learning outcomes of class IX.1 students of SMP Negeri 1 Wawo, Bima Regency, West Nusa Tenggara Province. Data were collected with pre-test post-test instruments, student activity observation sheets, and student opinion response questionnaires. Data were analyzed using descriptive statistical analysis. Data presentation is done in the form of frequency distribution tables and group explanations through mean, median, standard deviation, and percentage. The results of the post-test data analysis in cycle I number of students who completed were 19 students (79.16%), and those who had not completed were 5 students (20.83%) with an average score of 74.44. In cycle II the number of students who completed were 21 students (87.50%), and those who had not completed were 3 students (12.50%) with an average score of 76.46. This means that it has exceeded the minimum completeness criteria that have been set classically, namely 85% with an average value of 75.00. The results of the analysis of student motivation data in cycle I average score of attention during learning was 83.25 (very good), asking or expressing opinions was 71.25 (good), and participation in study groups was 82.25 (very good), with an average score -average 78.91 (very good). In cycle II, the average score of attention during learning was 85.67 (very good), asking questions or expressing opinions was 71 (good), and collaboration with peers/participation in study groups was 81 (very good), with an average score of 79 .22 (very good). Based on the results of the data analysis, it can be concluded that the genetic package can increase the motivation and learning outcomes of class IX.1 students of SMP Negeri 1 Wawo in learning about inheritance.